Optimizing Rice Seed (Oryza sativa L.) Production and Quality through Organic Fertilizer Application - Pradana, Farhan Novfourthino; Suhartanto, Mohamad Rahmad; Suwarto, Suwarto (Journal of Tropical Crop Science, 2026)
Rice (Oryza sativa L.) is a vital cereal crop and primary food source for over half of the global population, especially in Asia, Africa, and Latin America. This study evaluated the effect of organic fertilizers on optimizing rice seed production and quality. Organic fertilizers improve soil physical, chemical, and biological properties, thereby enhancing nutrient availability. A study was conducted standard and premium organic fertilizers (petroganik), in a completely randomized design with six treatments: no fertilizer (control), (12.5% organic C) at 500 kg/ha, and the premium organic fertilizer (15% organic C) at 250, 500, 750, and 1000 kg/ha. With four replications, 24 experimental plots were established. Results showed that while application of premium organic fertilizer did not affect vegetative growth, it significantly increased the number of productive tillers and overall yield. Applying 500 kg/ha of premium organic fertilizer increased rice yield by up to 13% compared to the control, with a relative agronomic effectiveness of >95%. Seed quality improved, indicated by higher germination rates, vigor index, and maximum growth potential. The after-ripening period was shortened by two weeks compared to control seeds, i.e., from 5 to 3 weeks, but did not affect seed storability.